A conceptual framework for environmental justice based on shared but differentiated responsibilities - Asghar Ali (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2001)
Environmental justice has become a major issue in the discourses of environment. The calls for environmental equity and justice are now part of major environmental negotiations like the UNFCCC and the Kyoto Protocol, to give some examples. In this paper I locate the issues of environmental justice within the broader framework of environmental sustainability and the contemporary debates about theories of justice. The environmental justice movement in the USA, which has gained popular momentum in recent years, is briefly studied. This particular grassroots movement appears to be redefining the sustainability agenda with a strong social justice content. It has similarities with environmentally informed social justice movements in the developing world, the so- called environmentalism of the poor. Employing a critical discursive methodology I briefly and critically review some of the well-known theories of justice based on different principles of justice like need, desert and entitlement. These are looked at within the contemporary debates of universalism versus particularism or the abstract liberal versus communitarian theories and some other critical perspectives on justice. I argue for a broader conception of environmental justice that takes into account particularities but is also sensitive to the global nature of many of the environmental problems that are spread and have impacts across regions, territories and even countries. In such situations it becomes necessary as a matter of justice to take into account differentiated impacts arising out of disproportionate contributions to environmental harms or bads. I further argue that a theory of justice, which will recognize this fact, will also have to consider differentiated responsibilities.
Keywords: 330; Sustainability; sustainable development; equity; justice; distributive justice; vulnerabilities; responsibility; Umwelt; Nachhaltige Entwicklung; Gerechtigkeit; Theorie